1986
DOI: 10.1002/jpln.19861490307
|View full text |Cite
|
Sign up to set email alerts
|

Einfluß der Cl‐Ernährung auf Ertrag und Nitratgehalt von Spinat und Kopfsalat

Abstract: Zusammenfessung -Summary Durch gezielte CI-Ernahrung konnte das zum Hochstertrag fiihrende N-Angebot bei Friihjahrsspinat von 250 auf 200 kg Nha, bei Herbstspinat von 200 auf 150 kg Nha vermindert werden, ohne daS es zu ErtragseinbuSen kam. Das optimale C1-Angebot des Bodens (Cl-Gehalt in 0-60 cm Bodentiefe + C1-Dungung) lag bei ca. 350 kg Cl/ha, wobei jedoch ein Cl-Angebot in der Krume (0-30 cm) von ca. 300 kg CYha nicht uberschritten werden sollte, weil sonst Auflaufschaden auftreten konnen. Da die Boden der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
2
4
1
Order By: Relevance
“…In the present study, increasing the nutrient solution concentration from 2 to 66 mequiv L −1 caused a linear increase in nitrate content, but the nitrate values in leaf tissues were never as high as the limit value of 4500 mg kg −1 FW imposed by the European Community. The high correlation between nutrient application rates (in particular N) and crop nitrate is in close agreement with the results of several earlier studies on lettuce grown in soil under both field39, 40 and greenhouse14, 41 conditions Moreover, low light levels are associated with nitrate accumulation in some leafy vegetables. For example, Chadjaa et al 42 and Gaudreau et al 43 reported that a reduction in light level was associated with reduced nitrate reductase activity and increased nitrate accumulation in lettuce and spinach.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, increasing the nutrient solution concentration from 2 to 66 mequiv L −1 caused a linear increase in nitrate content, but the nitrate values in leaf tissues were never as high as the limit value of 4500 mg kg −1 FW imposed by the European Community. The high correlation between nutrient application rates (in particular N) and crop nitrate is in close agreement with the results of several earlier studies on lettuce grown in soil under both field39, 40 and greenhouse14, 41 conditions Moreover, low light levels are associated with nitrate accumulation in some leafy vegetables. For example, Chadjaa et al 42 and Gaudreau et al 43 reported that a reduction in light level was associated with reduced nitrate reductase activity and increased nitrate accumulation in lettuce and spinach.…”
Section: Discussionsupporting
confidence: 91%
“…Partial replacement of NO 3 by chloride decreased the NO 3 content of both shoot and storage root. The reducing effect of Cl is due to the competition between Cl and NO 3 as has been suggested by Kirkby and Knight (1977), Wehrman and Hahndel (1984), Hahndel and Wehrman (1986), Stienstra(1986), Vander Boon et al (1990, Giines et al (1994), and Inal et al (1995). In the present study, calcium chloride increased the storage root nitrate content as compared to KC1, however, Maynard et al (1976) and Barker and Maynard (1971) have stated that Ca had no effect on nitrate accumulation.…”
Section: Discussioncontrasting
confidence: 51%
“…Chloride can partly replace NO 3 as an osmoticum (Roorda van Eysigna, 1984;Bloom-Zandstra and Lampe, 1983). Increasing the concentration of Cl in the nutrient medium can depress NO 3 uptake by the competition between these two ions (Hahndel and Wehrman, 1986;Stienstra, 1986;Van der Boon etal., 1990;Gunes etal., 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrification inhibitors together with ammonium and urea fertilizers tend to decrease the nitrate accumulation, but high rates ofnitrogen application involve a risk of ammonium toxicity (Goh and Vityakon 1983, Hähndel andWehrmann 1986 a). Kallio et al (1980) found that nitrapyrin caused a 30 % reduction of nitrate content.…”
Section: Discussionmentioning
confidence: 99%